Rancang Bangun Aplikasi Pemetaan WiFi Publik di Kabupaten Garut Berbasis Web GIS - Yosep Septiana; Dendi Mugia Iklas (Jurnal Algoritma, 2026)
The internet has become a basic necessity for society in the digital age, prompting the Garut Regency Government to launch a free public WiFi program based on Regent Regulation No. 119 of 2021 to realize a smart city. Currently, there are 62 public WiFi hotspots, but information on their locations and status is unclear, and there is no complaint mechanism to report disruptions. The Communication and Information Technology Agency (Diskominfo) faces difficulties in planning and evaluating WiFi placement due to limited data, hindering distribution adjustments. This research developed a Web GIS-based Public WiFi Mapping Application to support monitoring, data collection, and information delivery. The application was built using the Rational Unified Process (RUP) method with the stages of Inception, Elaboration, Construction, and Transition, and modeled with Unified Modeling Language (UML). The implementation uses the PHP language with the Laravel framework, MySQL, and the Leaflet library for map visualization. This application makes it easier for the public to find WiFi locations and report disruptions, as well as assisting the Communication and Information Agency in distribution planning. Beta testing showed a 98% satisfaction rate from the Communication and Information Agency and 97% from the public. Thus, this application is expected to overcome public WiFi management issues and facilitate access to services for the public.